2003
DOI: 10.1073/pnas.0835746100
|View full text |Cite
|
Sign up to set email alerts
|

Modular organization of internal models of tools in the human cerebellum

Abstract: Human capabilities in dexterously manipulating many different tools suggest modular neural organization at functional levels, but anatomical modularity underlying the capabilities has yet to be demonstrated. Although modularity in phylogenetically older parts of the cerebellum is well known, comparable modularity in the lateral cerebellum for cognitive functions remains unknown. We investigated these issues by functional MRI (fMRI) based on our previous findings of a cerebellar internal model of a tool. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
186
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(216 citation statements)
references
References 36 publications
22
186
0
4
Order By: Relevance
“…Previous functional imaging studies (Imamizu et al 2003(Imamizu et al , 2004 also supported the MOSAIC model and suggested that a prefrontal region (Brodmann area 46) contributes to the predictor while loops between the parietal regions (Pisella et al 2000) and the cerebellum contribute to the estimator. The current behavioral study in the context of previous computational (Wolpert et al 1995;Wolpert and Kawato 1998;Kawato 1999) and imaging studies (Imamizu et al 2004) suggests that, to achieve adaptation to multiple environments, a predictive mechanism, possibly located in the frontal cortex, needs to switch multiple internal models residing in the cerebellum.…”
Section: Discussionmentioning
confidence: 66%
“…Previous functional imaging studies (Imamizu et al 2003(Imamizu et al , 2004 also supported the MOSAIC model and suggested that a prefrontal region (Brodmann area 46) contributes to the predictor while loops between the parietal regions (Pisella et al 2000) and the cerebellum contribute to the estimator. The current behavioral study in the context of previous computational (Wolpert et al 1995;Wolpert and Kawato 1998;Kawato 1999) and imaging studies (Imamizu et al 2004) suggests that, to achieve adaptation to multiple environments, a predictive mechanism, possibly located in the frontal cortex, needs to switch multiple internal models residing in the cerebellum.…”
Section: Discussionmentioning
confidence: 66%
“…Recent investigations by Hutchinson et al (76) suggest that frequency and intensity of complex cognitive behaviors, such as music practice, correlate with increases in cerebellar volume. Additionally, cerebellar representational topography changes with exposure to new tools and related motor routines (77,78). As with skeletal morphology, it appears that variation in cerebellar morphology is partitioned between genetic factors and developmental and functional plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellum plays also a significant role in the early phases of acquisition and planning of motor sequences [Doyon et al, 2002], and is known to participate in a wide variety of cognitive and emotional processes [e.g., see Marien et al, 2001;Middleton and Strick, 1998;Rapoport et al, 2000;Salman, 2002]. Moreover, a modular organization of internal models of tool manipulation has been recently reported in the cerebellum using fMRI [Imamizu et al, 2003], extending the predictions of the MOSAIC computational model [Haruno et al, 2001;Wolpert and Kawato, 1998] from to the "motor" to the "cognitive" cerebellum. In the present study, we suggest that the vermian cerebellar activation associated with the innervatory pattern stage merely reflects its contribution to movement regulation [Deiber et al, 1996;Jueptner et al, 1996;Kitazawa, 2002] and integration of simple movements into more complex ones [Ramnani et al, 2001;Thach, 1998] during actual movement production.…”
Section: Innervatory Patternsmentioning
confidence: 96%